Dynamic analysis of structures with multiple tuned mass dampers - Lewandowski, Roman; Grzymisławska, Justyna (Journal of Civil Engineering and Management, 2009)
It is the purpose of this paper to analyse the possibility of reducing the vibrations of frame building structures with the help of multiple tuned mass dampers. Structures exposed to strong winds are considered. Excitation forces, which are functions of wind velocity fluctuations, are treated as random forces. The spectral density functions of wind velocity fluctuations are assumed as proposed by Davenport. The correlation theory of random vibration is used and the root mean squares of displacements and accelerations are determined. Several remarks, concerning the effectiveness of multiple tuned or mass dampers, are formulated from the results of calculation.Konstrukcijų su keliais masės slopintuvais dinaminė analizėSantrauka. Nagrinėjama galimybė sumažinti stipraus vėjo veikiamų rėminių pastatų konstrukcijų svyravimus, taikant masės slopintuvų sistemą. Vibracijas sukeliančios jėgos, priklausančios nuo vėjo greičio svyravimų, laikomos atsitiktiniais dydžiais. Vėjo greičio svyravimo spektro tankio funkcijos nagrinėjamos Davenport metodu. Atlikus atsitiktinių vibracijų regresinę analizę, nustatytos poslinkių ir pagreičių vidutinės kvadratinės paklaidos. Remiantis skaičiavimo rezultatais, padarytos masės slopintuvų efektyvumo išvados.Reikšminiai žodžiai: svyravimų mažinimas, atsitiktiniai svyravimai, masės slopintuvai.First Published Online: 14 Oct 2010